EFEKTIVITAS PERAN DINAS PERLINDUNGAN PEREMPUAN DAN ANAK DALAM PENCEGAHAN OCSEA (ONLINE CHILD SEXUAL EXPLOITATION AND ABUSE) DI WILAYAH KALIMANTAN TENGAH - Anis Aprilia; Ibnu Elmi as Pelu; Abdul Helim (PT. Hasba Edukasi Mandiri, 2025)
The advancement of digital technology presents a dual impact on children—on one hand, it offers vast opportunities for learning and interaction; on the other hand, it exposes them to serious threats such as Online Child Sexual Exploitation and Abuse (OCSEA). Central Kalimantan, with its vast geographical area, uneven digital literacy, and limited surveillance infrastructure, is particularly vulnerable to such online crimes. This article aims to examine the effectiveness of the Regional Office for Women and Children Protection (DPPA) in preventing and responding to OCSEA in Central Kalimantan. Using a descriptive-analytical approach, the study highlights four key strategies implemented by the DPPA: public education campaigns, cross-sector collaboration, complaint and victim support services, and local policy advocacy. Findings indicate that while the DPPA has initiated various programs, their overall effectiveness remains low due to limitations in human resources, funding, infrastructure, and inter-agency coordination. Strengthening institutional capacity, expanding outreach, and developing specific local regulations are essential to building a more robust child protection system against online sexual crimes.